Why Brussels? Neruda’s ‘título absolutamente enigmático’ - Moran, D (Taylor and Francis, 2024)
The primary purpose of this article is to propose a solution to longstanding literary mystery, namely, why Neruda’s disconcertingly enigmatic poem ‘Bruselas’ (from Tercera residencia [1947]) has a title which seems to bear little if any relation either to the city of Brussels itself or to its sometimes bewilderingly obscure content and imagery. The answer to this puzzle, I argue, lies deeply buried in Neruda’s biography—so deeply, however, that the core intelligibility of the text may be compromised as consequence. This raises questions concerning what might be deemed reasonable readerly competence in relation to both ‘Bruselas’ itself and, by extension, to some of the other, more hermetic, Residencia poems.